Application of adversarial risk analysis model in pricing strategies with remanufacturing - Liurui Deng; Bolin Ma (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: This paper mainly focuses on the application of adversarial risk analysis (ARA) in the pricing strategy with remanufacturing. We hope to obtain more realistic results than classical model. In fact, the classical Stackelberg model believes that since OEMs are the monopoly position, they know the pricing strategy of remanufacturers in the second period. However, the development of remanufacturing industry shakes OEMs' monopoly position and makes remanufacturers become stronger and stronger, so, in fact, OEMs don't know the pricing strategy of remanufacturers in the second period. Hence, the classical Stackelberg model isn't suited for reality. In this paper, we suppose that the OEMs don't know the pricing strategy of remanufacturers and recovery cost and only know their own information. Based on these assumptions, we predict the pricing strategy of remanufacturers from OEMs' point. Furthermore, we build OEMs' own pricing strategy based on the predicted the remanufacturers' pricing strategy, which is called OEMs' 1-order ARA model. Similarly, we look ourselves as remanufacturers and forecast OEMs' pricing strategy. Based on the forecasted OEMs' pricing strategy, we create the remanufacturers' own pricing strategy. Simulated results make us find ARA model gets more profit than classical Stackelberg model. Design/methodology/approach: In order to gain more actual research, we apply adversarial risk analysis to the pricing strategy with remanufacturing. As OEMs, they don't the recovery cost and the pricing strategy of remanufacturers, so they have to analyze and predict the pricing strategy of remanufacturers and based on this predicted the pricing strategy of remanufacturers build their own pricing strategy. The pricing strategy of OEMs is called 1-order ARA model of OEMs. To similar, remanufacturers build their own pricing strategy based on predicting the pricing strategy of OEMs. In the other words, remanufacturers build their own 1-order ARA model. Moreover, we use Monte Carlo simulation to numerically analyze and compare the 1- order ARA models with the classical Stackelberg models. Findings: We research the OEMfs 1-order ARA model with the uncertainty rate of recovery. That is, as OEMs, they donft know the recovery cost of remanufacturers and only know their own unit product cost c. So, they suppose the recovery cost is
Keywords: 650; pricing strategy; remanufacture; original equipment manufacturer; adversarial risk analysis